Formulasi dan Uji Stabilitas Sediaan Serum Kombinasi Ekstrak Lidah Buaya (Aloe vera Linn), Alpha Arbutin dan Niacinamide - Muhamad Naufal; Meiti Rosmiati; Hasna Latipah Sakinah (Jurnal Infokes, 2023)
The skin is an external organ of the body functioning physiologically crucial vulnerable to free radical exposure when the skin is exposed to intensive UV sunlight melanin production will increase the protective response and trigger pigmentation of the epidermal layer of facial skin. Aloe vera extract (Aloe vera Linn.), Alpha arbutin and Niacinamide have the ability to slow down the rate of melanosome pigment creation of melanin, increase skin brightness and high antioxidant content as an antipigmentation agent. The purpose of this study was to make a serum formulation of a combination of Aloe vera extract (Aloe vera Linn.), Alpha arbutin, Niacinamide gel preparations of variations in the concentration of aloe vera extract 5%, 10% and 15%. Serum preparations were evaluated for physical preparation, namely organoleptic test, homogeneity, pH, viscosity, spreadability, adhesiveness, storage stability. The research method is experimental research. The results showed that the combination serum of Aloe vera extract (Aloe vera Linn.), Alpha arbutin and Niacinamide can be made into serum preparations. The results of the evaluation of the physical properties of serum preparations obtained by the organoleptic test F1, F2, F3 are clear in color. F1 and F2 thick texture is slightly liquid, F3 thick texture. A weak aroma typical of aloe vera and homogeneous. F1 pH value 7 ±, F2 and F3 pH 8 ±. Viscosity F1 6249 mPa.S ± F2 6239 mPa.S ± F3 6256 mPa.S ±. Spreadability F1 and F2 4.9 cm ± F3 5.1 cm ±. Adhesion of F1: 1,91 ± F2 : 1.86 ± and F3: 1,79 ±. The combined serum preparation of Aloe vera extract, Alpha arbutin and Niacinamide formula F2 meets the requirements of physical characteristics and stability.